Cost-effectiveness analysis on the use of rFSH + rLH for the treatment of anovulation in hypogonadotropic hypogonadal women - Papaleo E; Alviggi C; Colombo GL; Pisanelli C; Ripellino C; Longobardi S; Canonico PL (Therapeutics and Clinical Risk Management, 2014)
Enrico Papaleo,1 Carlo Alviggi,2 Giorgio Lorenzo Colombo,3,4 Claudio Pisanelli,5,6 Claudio Ripellino,7 Salvatore Longobardi,8 Pier Luigi Canonico91Centro Scienze della Natalità, Gynecological-Obstetrics Department, San Raffaele Hospital, Vita-Salute San Raffaele, Milan, Italy; 2Department of Neuroscience, Reproductive Sciences and Odontostomatology, University “Federico II” of Naples, Naples, Italy; 3Department of Drug Sciences, University of Pavia, Pavia, Italy; 4SAVE Studi Analisi Valutazioni Economiche, Milan, Italy; 5ACO San Filippo Neri, Rome, Italy; 6Società Italiana Di Farmacia Ospedaliera, Milan, Italy; 7CSD Medical Research Srl, Milan, Italy; 8Medical Department, Merck Serono SpA, Rome, Italy; 9Department of Pharmaceutical Sciences, University of Piemonte Orientale, Novara, Italy Background: Hypogonadotropic hypogonadal women are characterized by ovarian functionality deficiency, caused by low concentrations of follicle-stimulating hormone (FSH) and luteinizing hormone (LH). To recover reproduction functionality, recommended therapies for ovarian induction involve injections of FSH and LH medications. Objective: Since important differences exist between recombinant and urinary gonadotropin therapies in terms of efficacy and cost, the objective of this study was to develop a cost-effectiveness model to compare recombinant FSH (rFSH) + recombinant LH (rLH) and highly purified human menopausal gonadotropin (HP-HMG). Methods: A Markov model was developed, considering three cycles of therapy; probability of pregnancy and miscarriage were considered, and the efficacy was evaluated in terms of pregnancy occurrence. The perspective of the model was that of the Italian Health Service, so only direct cost (drugs, specialist visits, patient examinations, and hospitalizations) were included. Results: rFSH + rLH is associated with a higher total cost (€3,453.50) and higher efficacy (0.87) compared with HP-HMG (€2,719.70 and 0.50). rFSH + rLH generated an incremental cost effectiveness ratio equal to €2,007.30 compared to HP-HMG; the average cost per pregnancy is estimated to be €3,990.00 for recombinant strategy and €5,439.80 for urinary strategy. Results of probabilistic sensitivity analysis were consistent with the abovementioned findings. Conclusion: Despite the higher acquisition cost in comparison to HP-HMG, rFSH + rLH resulted in a higher pregnancy rate, which makes it the recommended choice when considering cost-effectiveness of LH in supporting FSH-induced follicular gonadotropins in hypogonadotropic hypogonadal women. Keywords: HP-HMG, hypogonadotropic hypogonadism, gonadotropin